Academic Audit-A System for Quality Improvement - Ganorkar, S. R.; Gupata, B. L. (Journal of Engineering Education Transformations, 2008)
The quality of products of an institution and services of the institution is achieved through scientifically designed academic systems. Quality is never achieved as an accident. Sincere efforts, dedication and good intentions of the persons behind it, make quality. Quality concept is not new in India for education sector. It rests great responsibilities on the shoulders of educational institutions to demonstrate publicly that they are geared up to provide quality education and quality services to the society consistently for a long duration. It is, therefore, essential to develop the system that ensures the quality of the educational processes and consequently the quality of graduates. In the last two decades, it has been observed that the mushrooming growth of the large number of professional and technical institutions in the country with limited resources has affected the academic standards. The Quality can only be achieved by the education sector, when all the institutions come together and jointly design a mechanism, which assures the quality of graduates at par with to international standards. The quality of graduates can be assured through scientifically designed and implemented academic systems. The quality of processes can be assured using academic audit approach. In this paper an attempt is made to introduce Academic Audit as a system to assure and ensure the Quality of academic processes.